Influence of ethical ideology and emotional intelligence on the ethical judgement of future accountants in Malaysia - Ismail, Suhaiza; Rasheed, Zuhudha (Emerald Group Publishing Ltd., 2019)
Purpose – This paper aims to identify the influence of personal factors on the ethical judgement of future accountants in Malaysia. In particular, there are two research objectives for this study: first, to investigate the influence of ethical ideology on the ethical judgement of accounting students and second, to investigate the influence of emotional intelligence (EI) on ethical judgement. Design/methodology/approach – The respondents of the study were final year undergraduate accounting students from three public universities in Malaysia. A survey questionnaire comprising instruments about ethical ideology, EI and ethical judgement was distributed. A total of 205 responses were received and were deemed as useable. To achieve the research objectives, multiple regression was performed. Findings – The findings indicate that idealism and EI have a positive influence on the ethical judgement. In contrast, the study discovered that relativism influences ethical judgement negatively. Originality/value – This study fills the research gap as research on personal factors on the ethical judgement of future accountants is very limited and scarce. It gives insights to the various parties concerning how to enhance ethical judgement among future accountants, which ultimately will improve the credibility of the accounting profession.